One-step versus two-step impression techniques; a literature review - Razan Alshamrani; Alhanoof Aldegheishem; Elzahraa Eldwakhly; Mai S. Mostafa (Elsevier, 2019)
Objective: The aim of this literature review was to compare one-step impression technique versus two-step impression technique regarding their dimensional accuracy. Methodology: A Medline search was conducted through PubMed and Saudi Digital Library search engine using the following terms "impression techniques", "conventional techniques", "one-step", "two-step" and "accuracy". The search reviewed between 2008 and 20018. Twenty-nine articles were screened. Nine articles were assessed for eligibility out of which six were included. Results: Three articles found that one-step impression technique had better dimensional accuracy than two-step impression technique. While the other articles showed that two-step impression technique had better dimensional accuracy than one-step impression technique. Conclusion: Within the limitations of this review, both one-step and two-step impression techniques exhibited acceptable dimensional accuracy. There are still controversies about the accuracy of one-step impression technique versus that of two-step impression technique, so more extensive in-vivo clinical studies should be performed.